The zenithal 4-m International Liquid Mirror Telescope: a unique facility for supernova studies. Issue 2 (5th February 2018) - Kumar, Brajesh; Pandey, Kanhaiya L; Pandey, S B; Hickson, P; Borra, E F; Anupama, G C; Surdej, J
Abstract: The 4-m International Liquid Mirror Telescope (ILMT) will soon become operational at the newly developed Devasthal observatory near Nainital (Uttarakhand, India). Coupled with a 4k × 4k pixels CCD detector and TDI optical corrector, it will reach approximately 22.8, 22.3, and 21.4 mag in the g ΄, r ΄, and i ΄ spectral bands, respectively, in a single scan. The limiting magnitudes can be further improved by co-adding the consecutive night images in particular filters. The uniqueness to observe the same sky region by looking towards the zenith direction every night makes the ILMT a unique instrument to detect new supernovae (SNe) by applying the image subtraction technique. High cadence (∼24 h) observations will help to construct dense sampling multi-band SNe light curves. We discuss the importance of the ILMT facility in the context of SNe studies. Considering the various plausible cosmological parameters and observational constraints, we perform detailed calculations of the expected SNe rate that can be detected with the ILMT in different spectral bands.